An Accelerated Proximal Algorithm for the Difference of Convex Programming. (26th April 2021) - Shen, Feichao; Zhang, Ying; Wang, Xueyong
Abstract : In this paper, we propose an accelerated proximal point algorithm for the difference of convex (DC) optimization problem by combining the extrapolation technique with the proximal difference of convex algorithm. By making full use of the special structure of DC decomposition and the information of stepsize, we prove that the proposed algorithm converges at rate of O 1 / k 2 under milder conditions. The given numerical experiments show the superiority of the proposed algorithm to some existing algorithms.